467 FRAILTY IN SITU SIMULATION. (14th June 2021) - Dunnell, L; Chu, K; Barnard, A; Walker, G
Abstract: Introduction: The ability to recognise and manage frailty and its associated presentations is variable among acute hospital staff. Patients living with frailty who are admitted to hospital are more likely to suffer adverse effects than those without. We created an inter-professional in-situ simulation programme designed to improve recognition and management of frailty and its common adverse events. The programme objectives align with recommendations from the British Geriatric Society's 'Frailty Hub' and Royal College of Physicians' 'Acute Care Toolkit' for frailty. Method: Over a two month period, seven sessions were completed on the Older Persons Unit (OPU) at St Thomas' Hospital. These comprised a simulated scenario followed by facilitated debrief—including technical skills and human factors highlighted by the scenario. Quantitative data was collected through pre and post session questionnaires using the Human Factors Skills for Healthcare Instrument (HuFSHI) and frailty based questions. Post session qualitative data was also collected. Results: 30 participants attended the sessions (nursing, medical and allied health professional). All participants completing the post course questionnaire found the sessions useful. When comparing pre and post session data, participant confidence in 10/12 sections of the HuFSHI and 8/9 frailty based questions demonstrated improvement. The qualitative data showed common learning themes around improved communication, teamwork and escalation. Participants found that the sessions were a valuable 'opportunity to reflect' and 'debrief', and learn together as a multidisciplinary team. Conclusion: In-situ simulation is an effective tool for improving knowledge and confidence in managing frail patients. It increases awareness and understanding of human factors, which are key to the multidisciplinary approach frail patients require. The course is being expanded across the OPU and now has funding for a departmental manikin. The programme can be disseminated to other units to help improve the care and safety of those with frailty in hospital.